THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL COMMITMENT ON HIGH SCHOOL TEACHER PERFORMANCE IN PRINGSEWU DISTRICT - Alimi, Muhammad; Siswoyo, Siswoyo (Institut Bakti Nusantara, 2025)
This study aims to analyze the influence of transformational leadership and organizational commitment on the performance of high school teachers in Pringsewu Regency. Teacher performance is a key factor in improving the quality of education, influenced by the principal’s leadership style and the level of teachers’ organizational commitment. This research employs a quantitative approach with a survey method. Data were collected using questionnaires distributed to teachers from 10 high schools in Pringsewu Regency. Data analysis was conducted using simple and multiple regression techniques to examine the effect of each variable both individually and simultaneously. The results show that transformational leadership has a significant influence on teacher performance. Principals who are inspiring, supportive, and motivating contribute positively to improving teaching quality. Organizational commitment also plays an important role in shaping teachers' loyalty and dedication, which enhances their work effectiveness. Simultaneously, both variables significantly to improving teacher performance. The conclusion affirms that effective transformational leadership and high organizational commitment can significantly enhance teacher performance. The implication of this research is the need to strengthen school leadership competencies and implement strategies to increase organizational commitment contribute in order to create a more productive and high-quality educational environment.